MirGeneDB 2.1: toward a complete sampling of all major animal phyla. Issue Volume 50:Issue D1(2022) (25th November 2021) - Fromm, Bastian; Høye, Eirik; Domanska, Diana; Zhong, Xiangfu; Aparicio-Puerta, Ernesto; Ovchinnikov, Vladimir; Umu, Sinan U; Chabot, Peter J; Kang, Wenjing; Aslanzadeh, Morteza; Tarbier, Marcel; Mármol-Sánchez, Emilio; et al.
Abstract: We describe an update of MirGeneDB, the manually curated microRNA gene database. Adhering to uniform and consistent criteria for microRNA annotation and nomenclature, we substantially expanded MirGeneDB with 30 additional species representing previously missing metazoan phyla such as sponges, jellyfish, rotifers and flatworms. MirGeneDB 2.1 now consists of 75 species spanning over ∼800 million years of animal evolution, and contains a total number of 16 670 microRNAs from 1549 families. Over 6000 microRNAs were added in this update using ∼550 datasets with ∼7.5 billion sequencing reads. By adding new phylogenetically important species, especially those relevant for the study of whole genome duplication events, and through updating evolutionary nodes of origin for many families and genes, we were able to substantially refine our nomenclature system. All changes are traceable in the specifically developed MirGeneDB version tracker. The performance of read-pages is improved and microRNA expression matrices for all tissues and species are now also downloadable. Altogether, this update represents a significant step toward a complete sampling of all major metazoan phyla, and a widely needed foundation for comparative microRNA genomics and transcriptomics studies. MirGeneDB 2.1 is part of RNAcentral and Elixir Norway, publicly and freely available at http://www.mirgenedb.org/ .